Isotopic and hydrochemistry fingerprinting of leachate migration in shallow groundwater at controlled and uncontrolled landfill sites - Syafalni S.; Zawawi M.H.; Abustan I. (International Digital Organization for Scientific Information, 2023)
Hydrochemical and stable isotopic monitoring were performed in two different landfill sites, which are Matang and Beriah landfills for identifying leachate migration into shallow groundwater. The data provides information and allows inferences to be made on chemical characteristics of the contaminants, migration pattern of the groundwater and the difference between controlled landfill and open dumping which depends on the groundwater quality performances for landfill. A series of comprehensive hydrochemistry data was interpreted by using a piper and stable isotope relationship diagrams. Hydrochemistry parameters were major ions (Cl-, SO42-, NO3-, HCO3-, Mg2+, Na+, Ca2+ and K+) and for the stable isotopes consist of ?2H and ?18O. The pollutans of Matang landfill shows have the tendency to migrate and disperse toward the southeast side of the landfill site and Beriah landfill site shows that the contaminants tend to migrate to the south west. This result was parallel to the isotopic composition which shows mixing between shallow groundwater with leachate. The concentrations of heavy metals are more higher in Beriah landfill compared to Matang landfill. The significant difference is due to the type of landfill itself; Matang landfill operates as a sanitary landfill and Beriah Landfill operates as an open dumping. © IDOSI Publications, 2014.